Stroke in Adults With Coarctation of the Aorta: A National Population‐Based Study. Issue 11 (1st June 2018) - Pickard, Sarah S.; Gauvreau, Kimberlee; Gurvitz, Michelle; Gagne, Joshua J.; Opotowsky, Alexander R.; Jenkins, Kathy J.; Prakash, Ashwin
Abstract : Background: Adults with repaired coarctation of the aorta (CoA) have reduced long‐term survival compared with the general population. This study aimed to determine whether CoA is independently associated with premature ischemic and hemorrhagic stroke in the contemporary era. Methods and Results: This was a cross‐sectional study utilizing the National Inpatient Sample database from 2005 to 2014. We hypothesized that patients with CoA are hospitalized with ischemic and hemorrhagic stroke at a younger age compared with the general population. To test this hypothesis, we compared the age at stroke in patients with and without a diagnosis of CoA using simple and multivariable weighted linear regression. Among 4 894 582 stroke discharges, 207 had a diagnosis of CoA. Patients with CoA had strokes at significantly younger age compared with patients without CoA: 18.9 years younger for all‐cause stroke ( P <0.001), 15.9 years younger for ischemic stroke ( P <0.001), and 28.5 years younger for hemorrhagic stroke ( P <0.001), after adjusting for potential confounders. There was no significant difference in the proportion of ischemic strokes between those with and without CoA (79.2% versus 83.0%, P =0.50). However, CoA patients had a higher proportion of subarachnoid hemorrhage (11.8% versus 4.8%, P =0.039) than those without CoA. Among patients who had a hemorrhagic stroke, the prevalence of unruptured intracranial aneurysms was higher in patients with CoA compared with those without CoA (23.3% versus 2.5%, P =0.002). Conclusions: Patients with CoA have both ischemic and hemorrhagic strokes at significantly younger ages compared with the general population.